Retrospective Evaluation of Well Differentiated Thyroid Cancer Treatment Outcomes: 50 year experience at the University of Puerto Rico - Silva Frieda; Laguna-Figueroa Reinaldo; Ramirez-Vick Margarita; C. Negrón Juan; López Reynold; R Vázquez-Selles José (Journal of Thyroid Cancer, 2025)
Our study gathered information on the diagnosis, treatment, and long-term outcome in adult and pediatric Hispanic patients with Well Differentiated Thyroid Cancer. Methods We performed a retrospective review of the clinical and imaging nuclear medicine records of cases of WDTC evaluated and treated in the Nuclear Medicine CLINICc. Evaluation included the clinical PROFILE, histology, radioiodine (RAI) therapies and treatment response, long-term outcome and survival. The data was ASSESED using the 2015 ATA Risk level guidelines and recommendations. Results Three hundred eleven cases were reviewed, 81% females, 19% males, median age of 41 years. Eleven percent (34 patients) of the patients were in the pediatric group and 49% were between 16-45 years. The tumor histology was 60.5% Papillary, 28.2% Papillary-Follicular variant and 11.3% Follicular type. All patients had a total thyroidectomy. A total of 287 (92%) of the patients were treated with RAI. The median RAI dose was 128 mCi. Patients in the low risk group received a dose range of 25-105 mCi, 73 cases in the intermediate RISK group received 106-160mCi and 104 cases in the high-risk group received doses greater than 160 mCi. The overall median cumulative dose was 151 mCi (55-926 mCi). Annual follow up was done in all cases , WITH A median follow-up OF 5-10 years. Residual functioning tissue in the neck was found in 52% of the cases by US and/or RAI imaging. of those, 43% belonged to the low risk group, while 57% were in the intermediate and high-risk groupS. The mean treatment dose received by those with persistent functional thyroid tissue in the neck was 157 mCi. Recurrent disease was found in 15% of the patients, 85% of them belonged to the intermediate and high-risk GROUPS. Forty-seven percent of the patients with recurrent disease had residual disease. Conclusion We believe ablative and/or adjuvant RAI treatment early in the disease is important to decrease residual thyroid tissue and/or residual disease, and to improve disease-free survival. We recommend total thyroid surgery in all tumors above 1 cm, post-operative evaluation with RAI Whole Body (with 123-I or 131-I), planar and SPECT/CT imaging and RAI ablation to remnant tissue. Follow-up post treatment evaluation is also recommended.
Keywords: Thyroid Cancer Treatment